Forget tomorrow - Dunn, Pintip (Dunn, Pintip. Forget tomorrow, 2015)
On Callie's seventeenth birthday, she receives her vision of the future--a memory sent back in time to sculpt each citizen into the person they're meant to be. But Callie's vision shows her murdering her younger sister, and she is arrested and sent to a prison for those destined to break the law. Callie escapes and, on the run from the government and from her future, hoping to change her fate and protect her sister.